Aspectos morfo-tectônicos nos platôs de Portalegre, Martins e Santana/RN - Barros, Silvana Diene Sousa (1998)
A morpho-structural analysis was performed in the uplifted siliciclastic deposits of the Serra do Martins Formation along the Portalegre, Martins and Santana plateaux, in the southeastern and central regions of Rio Grande do Norte State. Due to the lack of biostratigraphic records, this formation has a disputable age.The adopted approach was based on the analysis of the drainage patterns and in the recognition of topographic surfaces and regional structures, subjected to neotectonic deformation and rejuvenation the present stress field. These events are recorded in the lineament arrays and as anomalous features of the landscape, such as the uplifted plateaux.The morpho-sculptural evolution of the studied blocks is expressed as erosive and accumulative processes. The former ones include erosional scarpments, cuestas and amphitheaters as the most characteristic features, while debris slopes represent acumulative examples. Such elements attest to the recent disequilibrium of the plateaux, and the absence of well developed alluvium terraces suggest an accelerated uplift process. The directions of the linear features observed in remote sensing products evidence the control of the basement structural trends, inherited from the pre-Cenozoic evolution. The NNE-SSW direction controls the main erosional features of the plateaux, while the N-S direction is a major drainage control, being also recognized in the Potiguar Basin. An E-W trend occurs as a less developed direction, reflecting either a system of mesozoic basic dykes or precambrian brittle structures. As regards to the drainage arrays, an arborescent, varying to a roughly N-S rectangular pattern, was identified in the Portalegre-Martins block. The Santana plateau displays rectilinear (northern border) and dendritic arborescent (southern border) patterns. In the sedimentary cover, the drainage pattern varies from rectangular to angular, reflecting inheritance from the crystaline basement. The most significative directions, N, NE and NW, mark the erosional fronts of the plateaux. Drainage anomalies, characterized by elbows or paralell confluencies, reinforce the arguments mentioned above. The data sets evidence the relationships between endogenous (lithology, structures) and exogenous features as the main controls of terrain dissecation, associated to vertical (epirogenesis) movements and horizontal tectonics. A final discussion addresses the relationships of the Serra do Martins Formation with the sedimentary record of Potiguar Basin, trying to establish chronostratigraphic links with the main evolutionary steps of this part of the Borborema Province, and possible mechanisms involved in the uplift of the plateaux and other stratigraphic units in the region